Evaluation of the Legibility of Wayfinding Signage in Mosques Through the Design of Ergonomic Signage - Bambang Suhardi; Afiq Ramadhan; Rahmaniyah Dwi Astuti (Journal of Islamic Architecture, 2026)
Mosque visitors often struggle with poorly designed wayfinding signs. Small fonts, unappealing color combinations, illogical placement, and dazzling materials contribute to this frustration. Common complaints involve signs for toilets, ablution areas, prayer halls, and holy boundaries. This study aimed to improve signage legibility by applying ergonomic principles. The visual display cognitive ergonomics approach was chosen, with a focus on human-system interaction and acknowledgment of human limitations. An experimental design was used to evaluate the effects of font size, typeface, and color combinations on legibility. Additionally, symbol comprehension tests and assessments of familiarity, compatibility, and standardization were conducted to inform the design of effective symbol signage. The experimental data were analyzed using the Friedman test. Spearman’s rank correlation test was used to assess the relationships among the three ergonomic factors: familiarity, compatibility, and standardization. Data analysis revealed that only font size significantly impacted legibility. However, a positive correlation was found between ergonomic factors and participant understanding of the signage symbols. This suggests that these factors collectively affect overall legibility. After introducing the newly designed signage, the study successfully increased sign legibility. Future research can explore additional factors that influence legibility to develop more comprehensive guidelines for mosque signage design.